Differential Lyn-dependence of the SHIP1-deficient mast cell phenotype. Issue 1 (December 2016) - Nunes de Miranda, Susana; Wilhelm, Thomas; Huber, Michael; Zorn, Carolin
Abstract Background Antigen (Ag)/IgE-mediated mast cell (MC) responses play detrimental roles in allergic diseases. MC activation via the high-affinity receptor for IgE (FcεRI) is controlled by the Src family kinase Lyn. Lyn-deficient (-/-) bone marrow-derived MCs (BMMCs) have been shown by various laboratories to exert stronger activation of the PI3K pathway, degranulation, and production of pro-inflammatory cytokines compared to wild-type (wt) cells. This mimics the phenotype of BMMCs deficient for the SH2-containing inositol-5'-phosphatase 1 (SHIP1). In this line, Lyn has been demonstrated to tyrosine-phosphorylate and activate SHIP1, thereby constituting a negative feedback control of PI3K-mediated signals. However, several groups have also reported on Lyn-/- BMMCs degranulating weaker than wt BMMCs. Results Lyn-/- BMMCs, which show a suppressed degranulation response, were found to exhibit abrogated tyrosine phosphorylation of SHIP1 as well. This indicated that even in the presence of reduced SHIP1 function MC degranulation is dependent on Lyn function. In contrast to the reduced immediate secretory response, pro-inflammatory cytokine production was augmented in Lyn-/- BMMCs. For closer analysis, Lyn/SHIP1-double-deficient (dko) BMMCs were generated. In support of the dominance of Lyn deficiency, dko BMMCs degranulated significantly weaker than SHIP1-/- BMMCs. This coincided with reduced LAT1 and PLC-γ1 phosphorylation as well as Ca2+ mobilization in those cells. Interestingly, activation of the NFκB pathway followed the same pattern as measured by IκBα phosphorylation/degradation as well as induction of NFκB target genes. This suggested that Ag-triggered NFκB activation involves a Ca2+ -dependent step. Indeed, IκBα phosphorylation/degradation and NFκB target gene induction were controlled by the Ca2+ -dependent phosphatase calcineurin. Conclusions Lyn deficiency is dominant over SHIP1 deficiency in MCs with respect to Ag-triggered degranulation and preceding signaling events. Moreover, the NFκB pathway and respective targets are activated in a Lyn- and Ca2+ -dependent manner, reinforcing the importance of Lyn for MC activation.